Flipped Classroom : Students' Cognitive Needs of Relatedness, Competence, and Autonomy in a Fully-Flipped Program. - Khosa, Amrinder; Burch, Steven (Journal of University Teaching & Learning Practice v.20 n.5 https://doi.org/10.53761/1.20.5.04, 2023)
This study examines how the flipped classroom approach to teaching and learning supports or inhibits the cognitive needs of relatedness, competence, and autonomy, leading to either increased or decreased levels of motivation. We use semi-structured interviews involving twenty-two students and five facilitators in an Australian university to qualitatively investigate perceptions of motivation through the lens of self-determination theory (SDT). Using thematic analysis, our findings reveal that the flipped classroom approach supports students' cognitive need for relatedness by providing more opportunities for interaction in the classroom. Further, relatedness has been shown to facilitate internalisation and support competence as a result of students supporting each other. However, our findings demonstrate that despite overall satisfaction with the flipped learning environment, the students raised concerns about how the learning is executed. Among recommendations for pedagogical practices, academics and education providers are urged to create an environment that supports a sense of belongingness and self-endorsement of learning activities among students to promote more autonomous forms of motivation. [Author abstract]